Time to work or time to play: the effect of student employment on homework, sleep, and screen time - Charlene Marie Kalenkoski; Sabrina Wulff Pabilonia (Institute for the Study of Labor (IZA), 2009)
We use detailed time-diary information on high school students' daily activities from the 2003-2008 American Time Use Surveys (ATUS) to investigate the effects of employment on the time a student spends on homework and other major activities. Time-diary data are more detailed and accurate than data derived from responses to 'usual activity' survey questions underlying other analyses and capture the immediate effects of working that may well accumulate over time to affect future outcomes. Our results suggest that employment decreases the time that high school students spend on human-capital-building activities such as homework and extracurricular activities, but also decreases screen time, which may be considered unproductive time. Results for sleep suggest that working teens may not suffer from reduced sleep time.
Keywords: J13; J22; J24; 330; Teenagers; employment; high school; time allocation; Studierende; Zeitbudgetforschung; Erwerbstätigkeit; Medienverhalten; Videospiel; USA